Potensi Sistem Absensi Berdasarkan Citra Wajah Sebagai Media Pengabdian Kepada Masyarakat - Ath-Thaariq, Bhakti; Fita Lestari, Riska; Mulyadi, Adi (Fakultas Teknik, Universitas PGRI Banyuwangi, 2022)
This paper describes the potential for attendance at Banyuwangi 1 State Vocational High School. The attendance system used is manual and does not optimal. The attendance based on face detector is proposed to determine the performance of employees and students. Face attendance is used to prevent employees from being absent from work and students not attending school. The results of the face detector show that the performance of employees and students can support the learning process in schools.